Analisis Demografi Pemegang Kartu Kredit Melalui Marketing Communication Pada BNI Card Center Surabaya - Wenti Krisnawati (Jurnal Manajerial, 2020)
Background - During a period that was very vulnerable to competition in the banking industry, it encouraged the banking industry to quickly adjust to the development of the needs and desires and demands of the surrounding community regarding banking products. Current developments in the use of credit cards occur quickly because there are many conveniences obtained from the use of credit cards. Research Objectives - To find out and determine the demographics of credit card holders in BNI based on marketing communication strategies. Design / methodology / approach- Research is focused on a qualitative approach with a case study methodology, the population in this study is BNI credit card holders, a sample of 21 BNI Credit card holders and using triangulation for data validity. Results and Discussion - The results of the interview data for choosing a credit card holder to use a BNI credit card are to shop and meet the needs of self-actualization rather than basic needs, the results of the interview also show that the concept of integrated marketing communication is that the customer knows and and ultimately has a BNI credit card due to advertising in electronic and digital media. Conclusion - Demographically the job as an entrepreneur / entrepreneur is a customer who has a lot of BNI credit cards and reasons to facilitate customer shopping activities. Implication research - Based on the results of the research that has been made, this research contributes to the marketing communication strategy in the banking business environment and other industries by paying attention to each element of demographic segmentation. Limitations research - For further research try to analyze more specifically about complaints on credit card payments because this research is very broad regarding marketing and demographic communication.